2019
DOI: 10.1016/j.cmi.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five methods for detection of carbapenemases in Enterobacterales with proposal of a new algorithm

Abstract: The aim of this study was to evaluate the performance of five different carbapenemase tests and to develop an algorithm which will permit the detection of most common and rare carbapenemases in routine microbiology laboratories. Methods: The immunochromatographic tests CARBA-5 (NG), RESIST-4 O.K.N.V. (Coris), the colorimetric b-CARBA (BioRad), a newly developed carbapenem-inactivation method (CIM) supplemented with zinc (zCIM), and the Xpert Carba-R (Cepheid) were challenged with a collection of 189 molecularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 26 publications
(26 reference statements)
3
98
3
1
Order By: Relevance
“…Our method originates from the CIM test, a simple and accurate assay recently developed to detect carbapenemase production in pure cultures of GN bacterial isolates. Various studies demonstrated a higher sensitivity of the CIM test and its improved variants over those of traditional colorimetric methods, especially for the detection of low-activity carbapenemases (26,31,32). As recently highlighted by Humphries (33), the interest of the clinical microbiology community regarding CIM-based tests is shown by the many articles posted on this topic since Breakpoints and interpretation criteria are as follows: for ES/ACBL/CARB-nonproducing EB, the MEM diameter was Ͼ15 mm and the CTX diameter was Ͼ14 mm; for ESBL/ACBL-producing EB, the MEM diameter was Ͼ15 mm and the CTX diameter was Յ12 mm; for carbapenemase-producing EB, the MEM diameter was Յ12 mm; and for disks with ATUs, the MEM diameter was 13 to 14 mm and the CTX diameter was 13 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Our method originates from the CIM test, a simple and accurate assay recently developed to detect carbapenemase production in pure cultures of GN bacterial isolates. Various studies demonstrated a higher sensitivity of the CIM test and its improved variants over those of traditional colorimetric methods, especially for the detection of low-activity carbapenemases (26,31,32). As recently highlighted by Humphries (33), the interest of the clinical microbiology community regarding CIM-based tests is shown by the many articles posted on this topic since Breakpoints and interpretation criteria are as follows: for ES/ACBL/CARB-nonproducing EB, the MEM diameter was Ͼ15 mm and the CTX diameter was Ͼ14 mm; for ESBL/ACBL-producing EB, the MEM diameter was Ͼ15 mm and the CTX diameter was Յ12 mm; for carbapenemase-producing EB, the MEM diameter was Յ12 mm; and for disks with ATUs, the MEM diameter was 13 to 14 mm and the CTX diameter was 13 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Rare carbapenemases (e.g., GES, IMI, GIM, and OXA-58) are currently not targeted by the two assays evaluated or most other commercially available PCR assays. Therefore, other diagnostic tests, such as the Carba NP test (20) or the zCIM test (4), which have previously proved to be sensitive for rare carbapenemase detection, are necessary to detect all CPE strains.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the ␤-lactamase (bla) genes encoding OXA-48-like, VIM, IMP, NDM, and KPC enzymes was analyzed for all strains by PCR and subsequent DNA Sanger sequencing, as described previously (4). For phenotypic identification of carbapenemases, a combination disk test (KPC and metallo-␤-lactamase [MBL] disk kit; Liofilchem, Roseto degli Abruzzi, Italy) was used as recommended by EUCAST (14), with meropenem and one of the following ␤-lactamase inhibitors: EDTA (MBL), cloxacillin (AmpC), or phenylboronic acid (class A).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations